The Students’ Perception of Technique Used by the Teacher in Teaching Speaking at Vocational High School - Gardini, Nosa Violeta; Hikmat, Mauly Halwat (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2024)
The research focused on students' perceptions of teaching techniques in English speaking skills at vocational high school in Kebumen. The method employed in this research is a descriptive method with a quantitative approach. The instrument used comprises 8 statement items crafted from the aspect of perception. Data analysis was conducted using descriptive statistical tests complemented by frequency distribution analysis. The sample for this research consisted of 86 students from grades XI at vocational school in Kebumen. The results showed varying perspectives among the students: Around 60.1% of students expressed positive views regarding the usefulness of diverse techniques employed in speaking practices, such as dialogues and role plays. Approximately 41.1% perceived teaching tools, including audio and visual aids, as supportive in comprehending speaking materials. Roughly 54.1% of students believed that the methods used, particularly those involving concrete examples and relevant exercises, facilitated their understanding of speaking materials. Concerning constructive feedback, 67.3% of students acknowledged its role in improving their speaking skills. Around 50.2% of the respondents supported the idea that the chosen teaching materials effectively assisted in their comprehension. A significant majority, approximately 89.9%, felt motivated to learn speaking due to the teacher's approach